2005
DOI: 10.1164/rccm.200409-1215oc
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Sputum from Adults and Children with Cystic Fibrosis and from Control Subjects

Abstract: We identified extensive protein degradation and differentially expressed proteins as biomarkers of inflammation relating to pulmonary exacerbations. Prediction of exacerbation onset and more precise evaluation of the extent of resolution with treatment could be achieved by including biomarkers in standard assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 57 publications
6
60
0
1
Order By: Relevance
“…This may lead to biomarkers of a higher mass being ignored. Other proteomics methods, such as twodimensional gel electrophoresis and immunocapture, may be better in assessing larger molecular weight proteins, and has been applied to CF (27,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may lead to biomarkers of a higher mass being ignored. Other proteomics methods, such as twodimensional gel electrophoresis and immunocapture, may be better in assessing larger molecular weight proteins, and has been applied to CF (27,29).…”
Section: Discussionmentioning
confidence: 99%
“…SELDI-TOF has been used to demonstrate protein expression in BAL in CF (25,26). There is as yet a lack of published data using SELDI-TOF to profile sputum, although complementary proteomic approaches of two-dimensional electrophoresis (27), shotgun protein sequencing (28), and affinity immunoproteomics (29) have been applied to sputum in an effort to discover new biomarkers.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Intense proteomics research to unveil protein markers has resulted in fi nding associations between myeloperoxidase, interleukin (IL)-8, cleaved ␣ -antitrypsin, and S100A8 (CF antigen) in sputum and the frequency of pulmonary exacerbations ( 7 ) or directly in the presence of CFTR mutations ( 8,9 ), in addition to proteomic signatures in serum or corresponding to known infl ammation markers ( 10 ) or other proteins differentially expressed in target tissues of CF before the appearance of any sign of the disease, like annexin-1 ( 11 ), cytosolic phospholipase A2 ␣ ( 11 ), cytokeratins 8 and 18 ( 12 ), and peroxiredoxin 6 ( 13,14 ). More recently, sputum proteomics has revealed that a prolineglycine-proline (PGP) peptide, an extracellular matrixderived neutrophil attractant, is a marker of infl ammatory clinical parameters at both time points.…”
mentioning
confidence: 99%
“…Interleukin (IL)-8 is the major neutrophil-attracting chemokine (11) present at high levels in airways of patients with CF (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). These high levels are likely to be responsible for abundant neutrophils in airway secretions of these patients (13,14,19,21,24,25).…”
mentioning
confidence: 99%